Assessment of economic benefits for EV owners participating in the primary frequency regulation markets - Bañol Arias, Nataly; Hashemi, Seyedmostafa; Andersen, Peter Bach; Træholt, Chresten; Romero, Rubén [UNESP] (Elsevier, 2020)
Transportation electrification plays an important role in developing more sustainable systems. As a result, the adoption of electric vehicles (EVs) is increasingly endorsed by governmental policies. It can be even more encouraged by promoting the provision of different ancillary services using vehicle-to-grid (V2G) enabled EVs, since EV owners may obtain additional profit by market participation. This paper presents an assessment of the economic benefits of using EVs to participate in the primary frequency regulation markets from the EV owner perspective. A heuristic method is proposed to optimize the power bid that maximizes the EV owners’ revenue along with a set of operational strategies that facilitates the service provision, which is evaluated using a simulation-based approach. A comparison analysis is performed to individually demonstrate the economic potential that four EVs with different battery capacities may offer to the owner when providing frequency-controlled normal operation reserves (FCR-N) in the Nord Pool market. The assessment of the power bid is performed considering the influence of the operation strategies and customer preferences. In addition, the effect of FCR-N on EV battery degradation and the grid impact caused by the service provision are considered in the economic evaluation. The results estimate annual benefits ranging between €100 and €1100 per vehicle, which demonstrates that EV owners can obtain substantial revenues by providing FCR-N.
Keywords: Battery degradation; Economic assessment; Electric vehicles; Frequency regulation; Operation strategies; V2G services